Flap motility as a sign of posterior capsule rupture in peripherally extended anterior capsular tears - Om Parkash R (Dove Medical Press, 2017)
Rohit Om Parkash,1 Shruti Mahajan,2 Vinod Biala,3 Tushya Om Parkash,4 Alhaj F Tasneem5 1Department of Cataract Surgery, 2Department of Cataract and Refractive Surgery, Dr Om Parkash Eye Institute, Amritsar, 3Department of Cataract Surgery, Eye Care Centre, Ghaziabad, 4Department of Cataract and Refractive Surgery, 5Department of Ophthalmology, Vydehi Institute of Medical Sciences and Research Centre, Bangalore, India Purpose: To describe various types of anterior capsular tears and an early diagnostic, flap motility, as a sign of posterior capsular rupture following posterior extension of radial tears. Design: This was a prospective study carried out in 4,331 eyes that underwent phacoemulsification in a private practice setting from April 2015 to February 2016. Twenty six consecutive cases of anterior capsular tears were included. Morphological features of anterior capsular tears and resultant complications were evaluated. Parameters studied were surgical step during which the tear occurred, shape of tear, its extension in relation to the equator, and flap nature and motility in tear extending up to equator. Main outcome measures: The main outcome measures were motility and nature of flaps in anterior capsular radial tears and the relation to posterior capsule rupture. Results: Based on shape, extent, and angulation, anterior capsular tears were categorized into 5 types: Type I, pre-equatorial radial tear (26.92%); Type II, post-equatorial radial tear (3.85%); Type III, Argentinean flag sign pre-equatorial tear (57.69%); Type IV, Argentinean flag sign post-equatorial tear (7.69%), and Type V, mini punch (3.85%). Flaps were either seen to be everted and fluttering or inverted and non-fluttering. In all cases with everted fluttering flaps no posterior capsular rupture (PCR) was observed, while in cases with inverted non-fluttering flaps a PCR was observed (p<0.05). Conclusion: Everted and fluttering flaps of the anterior capsular tears indicate pre-equatorial tear, while inverted and non-fluttering flaps indicate posterior capsule rupture following tear extension beyond the equator. Keywords: anterior capsule tear, posterior capsule rupture, flap motility sign, earliest sign